Research Variables and Their Classification: A Major Role in Scientific Methodology - Rani Asriyani; Hesti Widia Astuti (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
A variable in research refers to a measurable or observable characteristic or attribute that can vary between individuals, groups, or specific conditions. This study discusses various types of variables, including independent, dependent, and control variables, and the importance of operational definitions of variables in research. This research aims to provide a better understanding of how variables function in designing and conducting research, as well as their implications for the validity and reliability of research results. The findings indicate that appropriate variable selection and management are crucial for improving the quality and accuracy of research. The results of this study are expected to assist researchers in formulating and developing studies in the social and exact sciences.